The role of social capital in shaping green purchase intentions in the apparel industry - Zhou, Ziyu; Ahmad, Fauziah Sheikh (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of social capital on green purchase intentions within the apparel industry, integrating Social Capital Theory and Green Consumer Behavior Theory. We examine how trust, social norms, and social networks influence consumers’ willingness to buy eco-friendly apparel. Using regression analysis and Structural Equation Modeling (SEM), we analyze data from 320 Chinese consumers. Our results show that trust, social norms, and social networks significantly affect green purchase intentions, with social norms being the most influential factor. The findings suggest that building consumer trust, fostering positive social norms, and leveraging social networks are effective strategies for promoting sustainable consumption in the apparel industry. Businesses and policymakers can use these insights to develop initiatives that encourage green purchasing behavior, such as enhancing brand transparency, promoting sustainable consumption as a social norm, and utilizing digital platforms to disseminate information about eco-friendly products.